Metabolic reprogramming and apoptosis sensitivity: Defining the contours of a T cell response. (1st November 2017) - Voss, Kelsey; Larsen, Sasha E.; Snow, Andrew L.
Abstract: An effective adaptive immune response hinges on the rapid clonal expansion of T cells in response to antigen. The sensitivity of these T cells to programmed cell death (i.e. apoptosis) is carefully calibrated at various stages to ensure a robust yet measured reaction that resolves without inflicting unintended damage to host tissues. To meet bioenergetic demands associated with vigorous proliferation, acquisition of effector functions, and memory formation, T cells also undergo dynamic changes in their metabolism at every stage of this response. In this review, we focus on relatively recent studies that illuminate intimate links between metabolic programs and apoptosis sensitivity in T cells. We then examine how these connections ultimately influence T cell survival and function within the metabolically taxing environs of the tumor microenvironment. Highlights: T cells demonstrate dynamic reprogramming of their metabolism as an adaptive immune response unfolds. The magnitude of any T cell response is governed both by proliferation and apoptosis. Changes in T cell metabolism directly influence apoptosis sensitivity to regulate immunological memory and homeostasis. Stressful conditions of the tumor microenvironment force T cells to adapt their metabolism or succumb to apoptosis. Understanding these metabolic adaptations and their influence on T cell death may inform and improve new immunotherapies.